Presence of the past : memory, heritage and childhood in post-war Britain - Krips, Valerie, 1939- (Garland reference library of the humanities, 2000)
This book studies the interaction of heritage and fiction written for children over a forty year period in Britain. Examples range from new interactive displays in museums to historical re-enactment and the teaching of 'living history'.